1984
DOI: 10.1210/jcem-58-4-758
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenocorticotropin and Cortisol Responses to Ovine Corticotropin-Releasing Factor in Patients With Adrenocortical Insufficiency Due to Hypothalamic and Pituitary Disorders

Abstract: Plasma ACTH and cortisol responses to intravenous injection of 100 micrograms synthetic ovine corticotropin-releasing factor (CRF) were studied in 4 patients with hypothalamic hypopituitarism, 2 patients with Sheehan's syndrome, 2 patients with isolated ACTH deficiency and 10 normal subjects. All 4 patients with hypothalamic hypopituitarism had exaggerated plasma ACTH responses to CRF compared to normal subjects and gradual but definite increases in plasma cortisol from low basal levels. Of 2 patients with She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
10
0
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 7 publications
5
10
0
1
Order By: Relevance
“…The criterion for cortisol in this study is essentially the same as the criterion used by other authors. In addition, we recommend introducing the corticotropin releasing hormone (CRH) test to evaluate ACTH secretion [16][17][18]. Because CRH stimulates the pituitary gland, we can evaluate pituitary-adrenal function irrespective of hypothalamic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion for cortisol in this study is essentially the same as the criterion used by other authors. In addition, we recommend introducing the corticotropin releasing hormone (CRH) test to evaluate ACTH secretion [16][17][18]. Because CRH stimulates the pituitary gland, we can evaluate pituitary-adrenal function irrespective of hypothalamic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy is useful in preventing tumor recurrence, and many authors have reported its effects [18][19][20][21], but it has been reported that patients receiving irradiation were at higher risk of impairment of anterior pituitary function [19,22,23]. According to these reports, many patients developed impairment of function within five years after irradiation and some lost anterior pituitary function 8 or 9 years after irradiation [23].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (Tsukada et al, 1984b;Shulte et al, 1984a;Hermus et al, 1985a) have demonstrated that a single intravenous bolus injection of CRF reveals two subgroups of patients with secondary adrenal failure. The first of these have a pronounced and prolonged ACTH response, often expressed as a biphasic pattern with a delayed second peak, indicating that the cause of the adrenal insufficiency is not in the pituitary gland itself, but originates in the hypothalmus or at a higher level within the brain.…”
Section: Crf Stirnulation In Adrenal Insuficiencymentioning
confidence: 99%
“…Patients with the syndrome complain of symptoms resulting from the deficiency of multiple pituitary hormones. Hormonal examinations of those patients reveal that the site responsible for the deficiency of pituitary hormones is the pituitary itself [2][3][4][5][6][7].…”
mentioning
confidence: 99%